The Role of Islamic Education Teachers in Reinforcing Social Values among Public School Students in Jerash Governorate from the Point of View of Principals - Bani Salim, Afaf Mohammad Saleh (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the role of Islamic Education Teachers in reinforcing social values among public school students in Jerash Governorate from the point of view of principals, the study used the descriptive analysis approach, questionnaire has been used it consisted from (24) paragraph, the sample of study consisted from (120) female and male principals. However, the finding of study showed that the degree of Islamic educational role of Islamic Education Teachers in reinforcing social values was High with average (4.13. out of 5). The finding also showed there weren’t any significant difference at (α ≤ 0.05) in the degree of the role of Islamic Education Teachers in reinforcing social values among public school refers to variable of principal’s sex. Furthermore, there were significant differences according to principal’s years of experience for 10 years and more. In light of the results, the researcher recommended that educational officials should pay attention to social values and focus on them during training courses so that the participating teachers are clarified about the most important social values necessary for their students and ways to inculcate and develop them.